Distributed stochastic buffering for enterprise WLAN architectures. Issue 4 (1st February 2013) - Kim, J.H.; Ryu, E.‐S.
Abstract : The emergence of enterprise WLAN as a key technology has posed numerous challenges to researchers. Presented is a novel, theoretically‐grounded, distributed dynamic buffering mechanism to address two of those challenges, namely, buffer stability and power consumption costs. The proposed mechanism optimally controls the buffer dynamics of system switches, thereby guaranteeing buffer queue stability, and minimising time‐average expected power expenditure, thereby decreasing costs.